2009
DOI: 10.1002/eji.200939856
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apoptosis‐related genes in an Ethiopian cohort study correlates with tuberculosis clinical status

Abstract: Mycobacterium tuberculosis remains one of the world's deadliest pathogens in part because of its ability to persist in the face of an active immune response. It has been suggested that apoptosis of infected macrophages is one way in which the host deals with intracellular pathogens and that M. tuberculosis can inhibit this process. To assess the relevance of this process for human disease, we compared the expression of multiple genes involved in the activation of the extrinsic (''death receptor initiated'') pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
5
22
1
Order By: Relevance
“…[9][10][11][12][13][14]17,18 Several biomarkers identified earlier to discriminate between TB cases and LTBIs in German and South African cohorts (for example, FCGR1A (CD64), LTF and RAB33A), 13,19 were confirmed in the current study cohort from the Gambia. Intriguingly, FCGR1A is the only biomarker from our signature that was also identified by a recent large-scale microarray analysis in UK and South-African TB patients, 16 discriminating active TB disease from LTBI, despite being not specific for TB when compared with other inflammatory diseases.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[9][10][11][12][13][14]17,18 Several biomarkers identified earlier to discriminate between TB cases and LTBIs in German and South African cohorts (for example, FCGR1A (CD64), LTF and RAB33A), 13,19 were confirmed in the current study cohort from the Gambia. Intriguingly, FCGR1A is the only biomarker from our signature that was also identified by a recent large-scale microarray analysis in UK and South-African TB patients, 16 discriminating active TB disease from LTBI, despite being not specific for TB when compared with other inflammatory diseases.…”
Section: Discussionsupporting
confidence: 79%
“…Two independent dcRT-MLPA assays were performed on whole-blood RNA extracted from five PAXgene tubes collected from 12 Dutch healthy donors at two different time points. Variance component estimation was performed to calculate the contribution of the following four components to the variation in the gene expression profiles: (1) donor variation-the variation within a cohort of healthy individuals, (2) collection variation-the variation within the same healthy individual over time, (3) tube variation-the variation between the five separate PAXgene tubes collected from the same healthy donor, and (4) SPP1, BLR1, CCL19, MMP9, TIMP2), apoptosis-related genes differentially regulated by Mtb (TNFRSF1A, TNFRSF1B, BCL2, CASP8, TNF, FASLG), 14 genes that identify different lymphocyte subsets (CD3E, CD4, CD8A, CD14, CD19, NCAM1), regulatory T-cell-associated markers (FOXP3, IL7R, TGFB1, CTLA4, LAG3, IL10, CCL4, TNFRSF18, IL2RA), effector T-cell markers (IFNG, CXCL10) and reference genes (GAPDH, ABR, GUSB, B2M). Analysis of variance testing for global differences in gene expression profiles indicated significant differences between the study groups (P ¼ 5.4 Â 10 data set revealed profound differences in the overall gene expression profiles between TB cases versus LTBIs and TB cases versus uninfected healthy controls (Pp10…”
Section: Identification and Monitoring Of Biomarker Signaturesmentioning
confidence: 99%
“…Chemokines such as monocyte chemoattractant protein-1 are suggested to be involved in the massive monocyte recruitment to the lung to control M. tuberculosis infection [36,37]. A role for type I interferons in the accumulation of myeloid cell populations in the lung and pulmonary recruitment of inflammatory monocytes that lead to TB disease immunopathology has also been suggested [38][39][40]. An ongoing infection with an inadequate adaptive immune response against the pathogen may explain the increased percentage of blood monocytes observed in the TB contacts in our study prior to the development of active disease.…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory cytokine TNF- α is a crucial component for protection against M. tuberculosis , as shown by the rapid reactivation of latent M. tuberculosis infection in people treated with TNF- α receptor antagonists [89, 90] and the susceptibility of TNF- α -deficient animals to M. tuberculosis [5, 7]. Nonetheless, TNF- α mRNA is elevated in TB patients [4] and in TB/HIV-infected patients elevated levels of TNF- α were associated with necrosis [91]. It has been suggested that while it is essential for protection, that in the presence of elevated levels of IL-4, TNF- α appears to promote tissue damage rather than protection [19, 92], possibly by a cooperative effect of transcription [93, 94].…”
Section: Activating and Modulating The Adaptive Immune To M Tubermentioning
confidence: 99%
“…Though they are able to control the initial infection, they may later reactivate their disease if they become immunocompromised [3]. Infection with M. tuberculosis is associated with an active inflammatory immune response, characterized by elevated expression of both TNF- α [4–7] and IFN- γ [810]. These two cytokines are essential for controlling mycobacterial infections [1114] but it is clear that in many cases, M. tuberculosis is able to survive this inflammatory process.…”
Section: Introductionmentioning
confidence: 99%